The Role of Innovation Culture in Enhancing Employee Engagement: Evidence from Selected IT Firms - Manzoor, Mehnaz; Dhand, Shivani; Pandey, Aayushi (Journal of Neonatal Surgery, 2025)
This study explores the impact of innovation culture on employee engagement in selected IT firms, utilizing Structural Equation Modeling (SEM) to test the proposed hypotheses. Data was collected from 400 IT employees to analyze how a culture that encourages creativity, risk-taking, and continuous learning influences employee commitment, motivation, and job involvement. The findings indicate a strong positive relationship between innovation culture and employee engagement, emphasizing the significance of leadership support, knowledge-sharing mechanisms, and an adaptive organizational environment. Organizations that prioritize innovation create an atmosphere where employees feel valued, motivated, and empowered to contribute actively to business growth. The study highlights that fostering a culture of open communication, collaboration, and recognition enhances employee satisfaction and retention. Additionally, results suggest that firms with a strong innovation culture witness higher levels of employee participation in problem-solving, creativity, and performance excellence. The research provides valuable managerial implications, suggesting that IT firms should implement policies and practices that nurture an innovation-driven workplace, including flexible work environments, investment in continuous skill development, and incentives for innovative contributions. By strengthening the innovation culture, IT firms can enhance employee engagement, leading to improved productivity, reduced turnover, and long-term organizational success. This study contributes to the growing literature on workplace engagement and innovation, offering empirical evidence that supports the integration of innovation strategies to enhance workforce enthusiasm. Future research could further investigate the moderating effects of individual employee traits and organizational structures on the relationship between innovation culture and engagement in different industry settings.